2018
DOI: 10.1007/s00259-018-4139-4
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of pre-therapy 2-deoxy-2-18F-fluoro-D-glucose positron emission tomography-based radiomics classifiers of survival outcome in non-small-cell lung cancer patients

Abstract: PET-based radiomics classifiers derived from routine pre-treatment imaging possess intrinsic prognostic information for risk stratification of NSCLC patients to radiotherapy/chemo-radiotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
45
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 62 publications
(50 citation statements)
references
References 34 publications
2
45
0
1
Order By: Relevance
“…Early treatment response assessment and response and survival prediction is of interest to clinicians.as it may aid treatment selection and patient stratification, and justify a therapy switch. In 358 stage I-III NSCLC patients, Arshad et al used pre-therapeutic18F-FDG data from seven institutions to evaluate 18F-FDG-PET radiomics for overall survival (OS) prediction after radiotherapy or chemoradiotherapy (54).…”
Section: Clinical Outcome Predictionmentioning
confidence: 99%
“…Early treatment response assessment and response and survival prediction is of interest to clinicians.as it may aid treatment selection and patient stratification, and justify a therapy switch. In 358 stage I-III NSCLC patients, Arshad et al used pre-therapeutic18F-FDG data from seven institutions to evaluate 18F-FDG-PET radiomics for overall survival (OS) prediction after radiotherapy or chemoradiotherapy (54).…”
Section: Clinical Outcome Predictionmentioning
confidence: 99%
“…In one study, using 201 datasets and 43 textural features, the LASSO method was used and identified a single textural feature (SumMean) as an independent predictor of overall survival in large tumours treated with chemoradiotherapy [58]. In a further study of 358 datasets and 665 radiomic features, a similar LASSO methodology was used to derive predictive feature vectors that were tested on an independent validation set and predicted a 14-month survival difference [59].…”
Section: Nsclc: Defining Molecular Mechanisms From Imagingmentioning
confidence: 99%
“…Consequently, numerous additional prognostic or predictive factors [ 5 7 ], among image-derived parameters [ 8 12 ], have been investigated aiming at more differentiated outcome prediction and more differentiated management decisions. Among parameters from positron emission tomography/computed tomography with [ 18 F]fluorodeoxyglucose (FDG-PET/CT), asphericity (ASP) is a parameter that reflects shape irregularity of the primary tumor’s metabolic tumor volume (MTV), combining metric and metabolic features of the primary tumor.…”
Section: Introductionmentioning
confidence: 99%